Kepuasan Kerja di Kalangan Pengawal Keselamatan Universiti Pertanian Malaysia - Hasan, Ghazali; Suandi, Turiman (Universiti Putra Malaysia Press, 1995)
The purpose of this study was to determine the level of job satisfaction among security guards of Universiti Pertanian Malaysia and to determine predictors of job satisfaction among them. A questionnaire was used to measure the job aspects and job satisfaction level of 96 randomly selected UPM security guards. The data were processed using SPSS PC+. The independent variables included demographic characteristics, organizational factors and job dimension factors. The study showed that the majority of UPM security guards were moderately or highly satisfied with their job. The study also showed that factors such as organizational policies, opportunities for self-development, facilities at the work place, academic qualifications and job load were significantly related to job satisfaction level among the security guards. Organizational policy was the most important predictor of job satisfaction (R" = 0.50, P < 0.05), followed by opportunities to develop, facilities at the work place, academic qualifications and job load. The study also found that age, position, wages, tenure, job itself, promotion opportunities, supervision and peers are not predictors of job satisfaction level.